2021
DOI: 10.3389/fonc.2021.729207
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Shortening in Peripheral Leukocytes Is Associated With Poor Survival in Cancer Patients Treated With Immune Checkpoint Inhibitor Therapy

Abstract: BackgroundImmune checkpoint inhibitor (ICI) therapy represents a new standard of care for an increasing number of malignancies. Nevertheless, response rates and outcome of ICI treatment vary between individuals and the identification of predictive markers or hints towards immune cell exhaustion during therapy has remained a major challenge. Leukocyte telomere length is an established predictive biomarker of replicative aging and cellular proliferative potential in various hematological diseases. However, its r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…In a previous study, we found that low telomere length is associated with a higher risk of tumor onset ( 17 ). In the transplantation field, shorter telomere length in peripheral blood leukocytes was associated with a significantly worse clinical response in patients receiving immune checkpoint inhibitor therapy across different malignancies and the calculated relative telomere length differences defined as “delta telomere length” was found to be an independent predictor of overall survival ( 39 ). In our study, liver transplanted patients who developed a tumor presented a longer telomere length at baseline, but tended to undergo to a higher telomere erosion between the baseline and the tumor onset compared to LT-no-PTM patients during the same follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we found that low telomere length is associated with a higher risk of tumor onset ( 17 ). In the transplantation field, shorter telomere length in peripheral blood leukocytes was associated with a significantly worse clinical response in patients receiving immune checkpoint inhibitor therapy across different malignancies and the calculated relative telomere length differences defined as “delta telomere length” was found to be an independent predictor of overall survival ( 39 ). In our study, liver transplanted patients who developed a tumor presented a longer telomere length at baseline, but tended to undergo to a higher telomere erosion between the baseline and the tumor onset compared to LT-no-PTM patients during the same follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Cryopreserved whole blood cells after red blood cell depletion were used for the flow- fluorescent in-situ hybridization (flow-FISH) analysis of TL in lymphocytes and granulocytes (18). Alternatively, TL of colonies derived from CFUs, CD34 + and PBMC cell fractions were analyzed by telomere-PCR (TEL-PCR) (20).…”
Section: Methodsmentioning
confidence: 99%
“…The St. Jude Lifetime Cohort Study (SJLIFE) revealed a significantly shorter telomere length in leukocytes of childhood cancer survivors relative to that of the age- and sex-matched controls [ 54 ] . Patients with solid malignancies received immune checkpoint inhibitors revealed a link between peripheral leukocyte telomere shortening and poor survival [ 55 ] . Mammalian telomeres are protected by Shelterin, a protein complex composed of six proteins including TERF telomeric repeat binding factor 1 (TRF1) [ 56 ] , TERF telomeric repeat binding factor 2 (TRF2) [ 57 ] , telomeric repeat-binding factor 2-interacting protein 1 [TERF2IP, or repressor/activator protein 1 (RAP1)] [ 58 ] , the protection of telomeres 1 (POT1) [ 59 ] , TPP1 [ 60 ] , and TRF1-interacting nuclear factor 2 (TIN2) [ 61 , 62 ] .…”
Section: Telomere Shortening and Dysfunction In Cancer Survivorsmentioning
confidence: 99%